Molecular Imaging Probes for Diagnosis and Therapy Evaluation of Breast Cancer - Qingqing Meng; Zheng Li (International Journal of Biomedical Imaging)
Breast cancer is a major cause of cancer death in women where early detection and accurate assessment of therapy response can improve clinical outcomes. Molecular imaging, which includes PET, SPECT, MRI, and optical modalities, provides noninvasive means of detecting biological processes and molecular events in vivo. Molecular imaging has the potential to enhance our understanding of breast cancer biology and effects of drug action during both preclinical and clinical phases of drug development. This has led to the identification of many molecular imaging probes for key processes in breast cancer. Hormone receptors, growth factor receptor, and angiogenic factors, such as ER, PR, HER2, and VEGFR, have been adopted as imaging targets to detect and stage the breast cancer and to monitor the treatment efficacy. Receptor imaging probes are usually composed of targeting moiety attached to a signaling component such as a radionuclide that can be detected using dedicated instruments. Current molecular imaging probes involved in breast cancer diagnosis and therapy evaluation are reviewed, and future of molecular imaging for the preclinical and clinical is explained.